2013
DOI: 10.1038/ijo.2013.230
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of brown fat thermogenesis using chenodeoxycholic acid in mice

Abstract: CDCA could reverse obesity in cHF-fed mice, mainly in response to the reduction in food intake, an effect probably occuring but neglected in previous studies using cholic acid. Nevertheless, CDCA-dependent and food intake-independent induction of UCP1 in BAT (but not in WAT) could contribute to the reduction in adiposity and to the stabilization of the lean phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 40 publications
9
60
2
1
Order By: Relevance
“…This may mean that the magnitude of the increase in EE caused by iBAT nonshivering thermogenesis over a period of several weeks cannot be detected by indirect calorimetry but can be detected by the energy balance methodology of Ravussin et al (21). An additional question in the studies by both Watanabe et al (27) and Teodoro et al (24) comes from the lack of information on the ambient temperature in the former study, whereas the latter study was conducted at an ambient temperature of 20°C. Accordingly, does the EE/ thermogenic mechanism involve an interaction between the BAs, thyroid, and cold-activated adrenergic-mediated signaling pathways of thermogenesis?…”
Section: E349contrasting
confidence: 41%
See 1 more Smart Citation
“…This may mean that the magnitude of the increase in EE caused by iBAT nonshivering thermogenesis over a period of several weeks cannot be detected by indirect calorimetry but can be detected by the energy balance methodology of Ravussin et al (21). An additional question in the studies by both Watanabe et al (27) and Teodoro et al (24) comes from the lack of information on the ambient temperature in the former study, whereas the latter study was conducted at an ambient temperature of 20°C. Accordingly, does the EE/ thermogenic mechanism involve an interaction between the BAs, thyroid, and cold-activated adrenergic-mediated signaling pathways of thermogenesis?…”
Section: E349contrasting
confidence: 41%
“…The problem with the data of Watanabe et al (27) has been discussed by Teodoro et al (24), who, parenthetically, did not detect an increase in EE in mice fed BAs. Although Teodoro et al (24) showed a robust induction of Ucp1 expression in mice treated with BAs, whole body EE, as determined by indirect calorimetry, was not increased in diet-induced obese mice treated with BA. This may mean that the magnitude of the increase in EE caused by iBAT nonshivering thermogenesis over a period of several weeks cannot be detected by indirect calorimetry but can be detected by the energy balance methodology of Ravussin et al (21).…”
Section: E349mentioning
confidence: 99%
“…Elevated concentrations of cAMP activate type 2 deiodinase (D2), which converts the inactive thyroid hormone thyroxine to active 3-5-3 0 -triiodothyronine, thereby resulting in increased BAT activity and enhanced energy expenditure in murine BAT and human skeletal muscle (Watanabe et al, 2006). Indeed, the primary BA cholic acid increases whole-body energy expenditure in mice (Teodoro et al, 2014;Watanabe et al, 2006). Also in humans, an effect of BAs on energy expenditure has been proposed.…”
Section: Introductionmentioning
confidence: 96%
“…In both rodents and humans, BAT is targeted by bile acids. In C57BL/6 mice, dietary supplementation with cholic acid increased the thermogenetic capacity of BAT even in a thermoneutral environment and prevented diet-induced obesity (Teodoro et al, 2014;Watanabe et al, 2006;Zietak and Kozak, 2016). Mechanistically, the binding of bile acids to the TGR5 receptor increased the intracellular concentrations of the second messenger cAMP, which activates expression of the gene encoding for type 2 deiodinase (DIO2).…”
Section: Bile Acidsmentioning
confidence: 99%